A novel deformation mode of expansion tubes accounting for extra contact. (15th March 2023) - Tan, Bowen; Yao, Shuguang; Zhang, Lin; Xu, Ping; Che, Quanwei
Highlights: A novel conical die profile is explored for more contact length. Constraints are proposed to restrict the local deformation and fracture. The deformation and mechanical properties are investigated and compared with circular-die expansion tubes. A theoretical model is proposed for square-die expansion tubes based on energy method. Effect of the contact length on stability and the application of a square-die expansion tube on coupler are examined. Abstract: Expansion tubes are the main energy absorber of coupler and draft gear used on high-speed trains. With the rapidly increasing demand for energy-absorbing, the stroke is trying to extend without enhancing the action force. However, a stability problem occurred at one dynamic test due to the misalignment of coupler seats leading to the offset of load. The contact zone's structural strength of the conical die contributes much to lateral stability. A reasonable geometric configuration was investigated, and a square die was proposed. The square die has a longer conical surface and extra oblique line contact by filling the gaps between the tube and die. Quasi-static experiments, finite element simulations, and an analytical model were performed to investigate square-die expansion tubes' deformation and mechanical properties. The square-die expansion has a similar action force and specific energy absorption (SEA) as the circular-die expansion. At an expansion angle of 30°, the contact length of the square-die expansion tubes was 3∼17.34 times those of the circular-die expansion. In addition, the square-die expansion tube has a higher specific energy absorption than the circular-die expansion tube at the same contact length. The effect of the contact length on stability and the application of a square-die expansion tube on the coupler under the offset load condition were examined. The square-die expansion tube maintained stability even for the misaligned amount of the coupler seats of up to 60 mm. These achievements pave an effective way for the future design of long-stroke expansion tubes. Graphical abstract: Image, graphical abstract